Incisional surface quality of electron-beam irradiated cornea-extracted lenticule for stromal keratophakia: high nJ-energy vs. low nJ-energy femtosecond laser - Chan, Jian S.; Han, Evelina; Lim, Chris H. L.; Kurz, Arthur C.; Shuman, Jeremy; Liu, Yu-Chi; Riau, Andri K.; Mehta, Jodhbir S. (Frontiers in Medicine, 2023)
Introduction: Corneal lenticules can be utilised as an additive material for stromal keratophakia.However, following extraction, they must be reimplanted almost immediately or cryopreserved in lenticule banks. Electron-beam (E-beam) irradiated corneas permit room-temperature storage for up to 2 years, enabling keratophakia to be performed on demand. This study aims to compare the performance of high nano Joule (nJ)-energy (VisuMax) and low nJ-energy (FEMTO LDV) femtosecond laser systems on the thickness consistency and surface quality and collagen morphology of lenticules produced from fresh and E-beamed corneas.Methods: A total of 24 lenticules with -6.00 dioptre power were cut in fresh human donor corneas and E-beamed corneas with VisuMax and FEMTO LDV. Before extraction, the thickness of the lenticules was measured with anterior segment-optical coherence tomography (AS-OCT). The incisional surface roughness of extracted lenticules was analysed using atomic force microscopy (AFM) and scanning electron microscopy (SEM). Multiphoton microscopy was then used to assess the surface collagen morphometry.Results: The E-beamed lenticules that were cut using FEMTO LDV were significantly thicker than the fresh specimens as opposed to those created with VisuMax, which had a similar thickness as the fresh lenticules. On the vertex, they were 11% thicker than the fresh lenticules. The surface roughness (Rq) of E-beamed lenticules incised with FEMTO LDV did not differ significantly from the fresh lenticules. This contrasted with the VisuMax-fashioned lenticules, which showed notably smoother surfaces ( 36% and 20% lower Rq on anterior and posterior surfaces, respectively) on the E-beamed than the fresh lenticules. The FEMTO LDV induced less cumulative changes to the collagen morphology on the surfaces of both fresh and E-beamed lenticules than the VisuMax.It has been previously demonstrated that the low nJ-energy FEMTO LDV produced a smoother cutting surface compared to high nJ-energy VisuMax in fresh lenticules.Here, we showed that this effect was also seen in the E-beamed lenticules. In addition, lower laser energy conferred fewer changes to the lenticular surface collagen morphology. The smaller disparity in surface cutting quality and collagen disturbances on the E-beamed lenticules could be beneficial for the early visual recovery of patients who undergo stromal keratophakia.